Agronomic Performance of Four CIMMYT Wheat Genotypes in the Tropical Environment of Semarang Regency in Central Java, Indonesia - Banjarnahor, Dina; Kurnia, Theresa Dwi (Universitas Panji Sakti, 2024)
Several wheat genotypes collected by the International Maize and Wheat Improvement Center (CIMMYT) in Mexico can be introduced in the tropical regions of Indonesia to support national wheat production. Currently, four genotypes originating worldwide are available for introduction: CWI 10553, CWI 17903, CWI 89948, and CWI 8124. This research aims to identify the performance and yield of these genotypes grown in a controlled environment. Wheat seeds were cultured in MS medium then transplanted into a pot filled with mixture of soil and compost. Pot cultivation was carried out at a latitude of 800 m asl. Fertilizer was applied four times: 1) 2 g of guano during transplanting; 2) 2 g of guano + 1 g of urea + 1 g of ZA + 2 g of P2O5 + 1 g of KCl three weeks after transplanting, 3) 2 g of guano 6 weeks after planting, and 4) 1 g of urea + 1 g of ZA + 2 g of P2O5 + 1 g of KCl during grain filling. By the end of the growing season, 10 plants of CWI 10553, 2 plants of CWI 17903, 4 plants of CWI 89948, and 10 plants of CWI 8124 survived until grain production. CWI 8124 seemed to adapt well as indicated by its relatively high number of tillers, number of seeds per spike, and grain weight per plant. CWI 89948 was less adaptive as its height and productivity were relatively low. Generally speaking, two genotypes in the Semarang Regency of Central Java suggested for further study were CWI 8124 and CWI 10553.